Theoretical aspects of harmonization of interest, emotions and intellectual activity and training of future teachers (Pedagogy of Higher and Secondary Education, 2011)
In the article considered the question of harmonization of interest, intellectual and emotional factors, which raises the effectiveness of the professional training for future teachers.
Keywords: harmonization; interest; emotion; intellectual factor